1972
DOI: 10.1002/pen.760120108
|View full text |Cite
|
Sign up to set email alerts
|

Strength of short‐fiber reinforced composites

Abstract: The structural utility of short, glass fiber‐reinforced epoxy composities is experimentally investigated for fiber volume fractions from 0.15 to 0.5. The strength and stiffness of systems with randomly oriented fibers are compared with those of similar composites with aligned fibers. The ultimate strength of both types of material increses in a reasonably linear fashion with volume fraction up to 0.5. For all volume fractions in this range, strength of the random composites is slightly higher than the longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…While the experimental curve does not look like this, the ultimate stress and strain agree well with experiment. Figure 3 shows the predicted strength for a random-in-a-plane fiber orientation, along with experimental data from a brittle matrix, glassiepoxy system (32). The prediction provides a reasonably good (and conservative) engineering estimate of the strength.…”
mentioning
confidence: 95%
“…While the experimental curve does not look like this, the ultimate stress and strain agree well with experiment. Figure 3 shows the predicted strength for a random-in-a-plane fiber orientation, along with experimental data from a brittle matrix, glassiepoxy system (32). The prediction provides a reasonably good (and conservative) engineering estimate of the strength.…”
mentioning
confidence: 95%
“…This is due to the damage to the fibers which results from the close packing at high volume fractions ofthe fibers. There exists some analytical expressions for the prediction of tensile strength of randomly oriented fiber composites, but it has been shown that these expressions do not adequately fit the experimental results (5).…”
Section: Impact Propertiesmentioning
confidence: 99%
“…Thus these properties typically depend on properties of constituent fibers and the matrix, the dispersion and contents of reinforcement fibers, and the interfaces between the reinforcement and the matrix. There are many publications [8][9][10][11][12] dedicated exclusively to short fiber reinforced thermoplastic polymer composites, however there are a little publications related to the paper made of short fibers reinforced composites.…”
Section: Introductionmentioning
confidence: 99%